Description of the Level of Knowledge and Attitudes of the Elderly About Rheumatoid Arthitis - Fricilia Sani Putri, Gina; Mahaputra, M. Ridho (Dinasti Health and Pharmacy Science, 2023)
The purpose of this study was to describe the level of knowledge and attitudes of the elderly about rheumatoid arthritis. This research uses a descriptive method. The population is all the elderly who are in the Posyandu Elderly Housing Complex of the Balaibaru Police Working Area of the Belimbing Padang Health Center with a total sample of 82 elderly. The results showed that 78% of the elderly had good knowledge about rheumatoid arthritis and 64.4% of the elderly had a positive attitude about rheumatoid arthritis. Research on the description of the level of knowledge and attitudes of the elderly about rheumatoid arthritis has obtained good results, for this reason it is hoped that the Belimbing Padang Health Center can improve the provision of much more and more information about rheumatoid arthritis in order to improve the health status of the elderly much better better than before.